Isolation and in vitro investigation on lactic acid bacteria for potential probiotic properties from cat feces - Wang, Jiali; Yang, Xue; Peng, Yi; Zhang, Jingyi; Huang, Yixin; Zhong, Zhijun; Liu, Haifeng; Fu, Hualin; Zhou, Ziyao; Peng, Guangneng (Frontiers in Veterinary Science, 2024)
BackgroundProbiotics, which are beneficial to the host, have been shown to benefit the health of cats. Lactic acid bacteria (LAB) are commonly used probiotics, but most strains used for cats are not derived from cats, leading to reduced efficacy and poor adaptation to cats. The objective was to identify LAB with promising probiotic potential specific to cats.MethodLABs were isolated from fecal samples of 20 healthy cats. Gram staining and the survival rate in the simulated gastrointestinal tract were used for preliminary screening. Candidate strains were identified by 16S rDNA sequencing, and further evaluated for adhesion ability, growth characteristics, antibacterial activity, antioxidant capacity, and safety.Results24 Gram-positive isolates were identified, with 10 (F1-F10) showing robust viability in the simulated gastroenteric fluid. These 10 strains exhibited excellent adhesion to Caco-2 cells and strong auto-agglutination properties. They also possessed the capacity to antagonize and aggregate pathogens (Staphylococcus aureus ATCC 25923, Salmonella Braenderup H9812, Escherichia coli ATCC 25922, and Pseudomonas aeruginosa PAO1), Moreover, all strains demonstrated tolerance to H2O2 concentrations ranging from 0.5–2 mmol/L and the ability to scavenge 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radicals, indicating a certain level of antioxidant activity. Safety tests showed no hemolytic activity, and all but F6 were highly sensitive to antibiotics, with over 62.5% sensitivity to 16 antibiotics. Remarkably, F4 (Lactobacillus reuteri) and F10 (Lactobacillus brevis) exhibited exceptional viability in the simulated gastrointestinal tract, coupled with robust growth potential, enhanced adhesion efficiency, significant antibacterial and antioxidant properties.ConclusionOur findings revealed that F4 (Lactobacillus reuteri) and F10 (Lactobacillus brevis) hold promising potential as probiotics. This research lays a solid scientific foundation for the selection and application of probiotics tailored specifically for cats.